Causes of death in infants born to women affected by Covid-19 disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The severity of the problem: The spread of the COVID-19 disease worldwide during the pandemic has resulted in the identification of harmful events in most pregnant women and fetuses through laboratory testing for SARS-CoV-2. This, in turn, leads to significant maternal complications in the field of medicine.